Удосконалення логістичних систем для забезпечення принципів стійкого розвитку підприємства - Курбацька, Лариса Миколаївна; Kurbatska, Larysa; Кадирус, Ірина Григорівна; Kadyrus, Iryna; Савенко, Олена Анатоліївна; Savenko, Olena; Нечипоренко, Костянтин Володимирович; Nechyporenko, Kostiantyn (Дніпровський державний аграрно-економічний університет, 2021)
Для забезпечення принципів стійкого розвитку, запропоновано використовувати напрями удосконалення логістичних систем підприємства, які включають такі складові: економічну (напрям розвитку: комерційно-стійкий, фінансово-стійкий, організаційно-стійкий, виробничо-технічно-стійкий та інноваційно-стійкий); соціальну (напрям роз витку: кадрово-стійкий та доходно-стійкий) та екологічну (напрям розвитку: ресурсно-стійкий та навколишньо-стійкий). Доведено, що забезпечення сталого розвитку підприємства, стабільності результатів його діяльності, досягнення цілей, що відповідають інтересам керівництва і суспільства загалом, неможливе без розробки і впровадження комплексу стратегічних заходів, реалізація яких обумовлюється рівнем логістичної інфраструктури і призводить до необхідності розгляду проблем ефективного управління підприємством. It is determined that the realization of strategic goals of the enterprise becomes possible when creating such logistics systems that would be aimed at achieving a high level of customer service, would optimize its material, information, financial flows and thus significantly reduce costs. This will allow to develop modern technologies of logistics management and to increase the economic efficiency of the enterprise. It is established that in the process of strategic management of sustainable development of the enterprise it is expedient to be guided by basic and complementary principles. To build a more efficient logistics system of a manufacturing enterprise, it is necessary to substantiate and prepare a project, which should consist of several successive stages. It is determined that the main directions of improving the logistics system of enterprises will be the principles of a systematic approach, revealed in the integration and clear interaction of all elements of the logistics system. The synthesis of the logistics system using a systems approach should be presented in the form of stages, the implementation of which will allow this process to consistently and timely adjust the goals, objectives and models of management decisions at each stage of the synthesis. To ensure the principles of sustainable development, it is proposed to use areas of improvement of logistics systems of the enterprise, which include the following components: economic (direction of development: commercially sustainable, financially sustainable, organizational-sustainable, production-sustainable and innovation-sustainable) social (development direction): personnel-sustainable and income-sustainable) and environmental (direction of development: resource-sustainable and environmentally sustainable). It is proved that ensuring sustainable development of the enterprise, stability of its results, achieving goals that meet the interests of management and society as a whole is impossible without the development and implementation of a set of strategic measures, the implementation of which is determined by the level of logistics infrastructure and leads to effective management.
Improvement of logistics systems to ensure the principles of sustainable enterprise development
Keywords: логістична діяльність; logistic activity; логістика; logistics; логістичні послуги; logistics services; логістична система; logistics system; підприємство; enterprise